O papel das redes sociais na migração contemporânea de gaúchos em Roraima - STAEVIE, Pedro Marcelo (Universidade Federal do Pará, 2019)
This study’s main aim was to understand and to explain the role of social networks in the contemporary migration of Gauchos to Roraima. Since the 1960s there has been an increase in the number of people borne in Rio Grande do Sul that reside in this state. During the years 1970, 1980 and 1990, some incentives and calls were fundamental to the migration of Gauchos to Roraima, namely: Project Rondon, the Advanced Campus of the Federal University of Santa Maria, the Military Police of Roraima, the Armed Forces and the agricultural colonization project. Currently, from an a priori stance, there is no evidence of attractive forces that they could motivate Gauchos to reside in Roraima. Yet the flow of Gauchos to this state is reflecting a steady increase. We try to understand why this has been occurring. Although the incentives and calls are finished, the migration of Gauchos to this state, which is so different and with so little appeal, continues to increase. This is what we tried to understand in this current research. The research focused on Gauchos who arrived between 2000 and 2011 in Roraima. A total of twenty-eight (28) heads of households were interviewed. For comparative purposes we further interviewed ten (10) Gauchos who had arrived in the years 1970, 1980 and 1990. The methodological approach was based on the analysis of oral reports given by respondents. Additionally, there were bibliographic and documentary reviews, and population data elicited from official sources. However, to understand migration as a social fact, a historical analysis of the socioeconomic and demographic transformations of the states of origin and destination, RS and RR, respectively was first done. Secondly, a historical review was conducted on the migration of Gauchos to the Amazon and to Roraima in particular, during the 1970s and 1980s. Finally, the analysis of contemporary migration among Gauchos to Roraima, based on oral reports given by respondents, was undertaken. The findings confirm that social networks of kinship, friendship and place of origin play a central role in this migratory flow and are therefore crucial for the adaptation and fixation of migrants in Roraima. Given the conditions and economic structure of Roraima State, the research confirms that the Gauchos who currently migrate to Roraima depend on social relations that have been established with gauchos already residing in this state. Without these ties Gauchos would not be migrating to resettle in Roraima.